Three-level experimental approach for creep and shrinkage of high-strength high-performance concrete. (1st August 2016) - Pan, Zuanfeng; Meng, Shaoping
Graphical abstract: Technical route of three-level experiment. Highlights: Proposing a three-level experimental approach for creep and shrinkage of concrete. Grouping specimens on three levels: "material level", "component level" and "structural level". Obtaining modified creep and shrinkage models based on the three-level experiment. Abstract: Most of the existing prediction models for creep and shrinkage are established based on the statistical regression analysis of test data drawn mostly from experiments performed on normal-strength concrete, and they might not be as applicable to high-strength high-performance concrete. The prediction precision can be improved by carrying out on the given concrete short-term creep and shrinkage measurements. A three-level experimental approach for creep and shrinkage is proposed in this study. Take the high-strength high-performance concrete used in the auxiliary shipping channel bridge of Sutong Bridge for example, the detailed three-level experimental process and results were presented. The specimens were grouped on three levels: "Material level", "Component level" and "Structural level". On the first level, plain concrete specimens were experimented in a constant temperature and constant humidity room. On the second level, creep and shrinkage of reinforced concrete specimens with different reinforcement ratio were experimented. On the third level, the long-term behavior of a segmental concrete cantilever beam, 12.8 m long, under natural environment which was close to that of the actual bridge was studied. This experimental approach can provide a new train of thought to improve the predicted precision of the creep and shrinkage effects of the long-span concrete structures.